Switchgrass (Panicum virgatum L.) Cultivar Adaptation, Biomass Production, and Cellulose Concentration as Affected by Latitude of Origin. (24th October 2012) - Jefferson, Paul G.; McCaughey, W. Paul
Abstract : Ten cultivars of switchgrass ( Panicum virgatum L.) of northern and southern origins that had demonstrated adaptation to North Dakota were evaluated for biomass production, cellulose concentration, and nutritive value in the southern Canadian prairie region: Saskatchewan and Manitoba. In this region, cultivars adapted to northern latitudes present interest for biomass production. Latitude of origin of the cultivars was positively correlated to stand density (r = 0.83, P < 0.01 ), biomass production (r = 0.69, P < 0.01 ), and cellulose (r = 0.84, P < 0.01 ), and negatively correlated with organic matter digestibility (r = − 0.86, P < 0.01 ) and N (r = − 0.85, P < 0.01 ). Dacotah and ND 3743, the northern origin cultivars, were more persistent in Brandon, MB (94 to 100% stand density) and exhibited higher cellulose and hemicellulose concentrations than southern cultivars. Southern cultivars produced higher biomass than northern-origin cultivars until they suffered significant stand and biomass decline. Cave-in-Rock, the southern origin cultivar, did not persist in the third year after seeding. However, southern-adapted cultivars exhibited better nutritive value for grazing cattle. We conclude that switchgrass production in the southern Canadian prairie should utilize the USA cultivars from northern latitudes or adapted Canadian cultivars should be developed.